Difference in organoleptic test results and antioxidant activity in variations of the method of making Emprit Ginger and Secang Wood powdered drink - Mia Srimiati; Sandra Hakim Afrizal; Sartika Mahardika (AcTion: Aceh Nutrition Journal, 2023)
Antioxidants in ginger (Zingiber officinale) and sappan wood play roles in health benefits, including dilating blood vessels and inhibiting cancer cells. The study analyzes the differences in organoleptic characteristics and antioxidant activity of powdered ginger and sappan wood, comparing Crystallization (MK) and conventional drying (MP) methods. In the crystallization method, 100 grams of Emprit Ginger and 5 grams of sappan wood sticks were blended, followed by adding 500 ml of water and 50 grams of sugar, then stirred in a hot pan for 2 hours until crystals formed. In the conventional drying method, an equal amount of ginger was dried for 5 days, and then, together with sappan wood and sugar, it was ground using a food processor. The data from the organoleptic test were normal, and the T-test result showed that powdered drinks from the drying method significantly exhibited better hedonic quality (p<0,05). For every 100 grams, this powder contains 386 kcal of energy, 1,62% ash content, 2,18% moisture content, 91,88% carbohydrates, 1,0% fat, 2,32% protein, and 2040,86 mg/kg of antioxidant activity (IC50 method). In conclusion, different methods affect the characteristics of ginger powder, which has implications for product development and medicinal uses.Keywords: